Amyloid-beta aggregation implicates multiple pathways in Alzheimer’s disease: Understanding the mechanisms - Iliyasu, Musa O.; Musa, Sunday A.; Oladele, Sunday B.; Iliya, Abdullahi I. (Frontiers in Neuroscience, 2023)
Alzheimer’s disease (AD) is a progressive neurodegenerative condition characterized by tau pathology and accumulations of neurofibrillary tangles (NFTs) along with amyloid-beta (Aβ). It has been associated with neuronal damage, synaptic dysfunction, and cognitive deficits. The current review explained the molecular mechanisms behind the implications of Aβ aggregation in AD via multiple events. Beta (β) and gamma (γ) secretases hydrolyzed amyloid precursor protein (APP) to produce Aβ, which then clumps together to form Aβ fibrils. The fibrils increase oxidative stress, inflammatory cascade, and caspase activation to cause hyperphosphorylation of tau protein into neurofibrillary tangles (NFTs), which ultimately lead to neuronal damage. Acetylcholine (Ach) degradation is accelerated by upstream regulation of the acetylcholinesterase (AChE) enzyme, which leads to a deficiency in neurotransmitters and cognitive impairment. There are presently no efficient or disease-modifying medications for AD. It is necessary to advance AD research to suggest novel compounds for treatment and prevention. Prospectively, it might be reasonable to conduct clinical trials with unclean medicines that have a range of effects, including anti-amyloid and anti-tau, neurotransmitter modulation, anti-neuroinflammatory, neuroprotective, and cognitive enhancement.